The influence of total quality management on organizational performance mediated by competitive advantage in SMEs - Yusabri; Firman Firman (Universitas Negeri Padang, 2021)
This research aims to analyze: 1) the influence of total quality management on organizational performance in the creative industries SME sector in Padang City, 2) the influence of total quality management on competitive advantage in the creative industries SME sector in Padang City, 3) the influence of competitive advantage on organizational performance in the creative sector of SMEs in Padang, 4) The influence of quality management on organizational performance is mediated by competitive advantage in Padang SMEs. This research is quantitative. The population in this study is the SME creative industries sector in Padang. Sampling techniques in this study are purposive sampling techniques. The number of samples used is 210 units of SMEs. The research data collected used questionnaires were then analyzed with SmartPLS version 3.3.3. This research is different from other studies, where the difference is the selection of research objects because most similar studies only examine MSMEs in general. In contrast, this study focuses more on the MSME sector of the creative industries. The results of this study show that: (1) total quality management has a significant effect on organizational performance in the creative industries MSMEs in Padang City, (2) Total quality management has a significant effect on competitive advantage in creative industries in Padang City, (3) Competitive advantage has a significant effect on organizational performance in creative industry SMEs in Padang City, (4) Competitive advantage mediates the effect of total quality management on organizational performance in creative industries SMEs in Padang City.